2021
DOI: 10.3390/nano11123255
|View full text |Cite
|
Sign up to set email alerts
|

Humulus scandens-Derived Biochars for the Effective Removal of Heavy Metal Ions: Isotherm/Kinetic Study, Column Adsorption and Mechanism Investigation

Abstract: Humulus scandens was first adopted as a biomass precursor to prepare biochars by means of a facile molten salt method. The optimized biochar exhibits a high specific surface area of ~450 m2/g−1, a rich porous structure and abundant oxygen functional groups, which demonstrate excellent adsorption performance for heavy metal ions. The isotherm curves fit well with the Langmuir models, indicating that the process is governed by the chemical adsorption, and that the maximum adsorption capacity can reach 748 and 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…They could be presented by Equations () and (), respectively. [ 32,33 ] Ceqegoodbreak=1qmaxKLgoodbreak+Ceqmax lnqegoodbreak=lnKFgoodbreak+1nlnCe where q max (mg/g) is the maximum adsorption capacity of Cu(II); K L (L/mg) is the Langmuir constant; K F (mg 1−1/ n ·L −1/ n ·g −1 ) is the Freundlich constants and n is Freundlich index.…”
Section: Resultsmentioning
confidence: 99%
“…They could be presented by Equations () and (), respectively. [ 32,33 ] Ceqegoodbreak=1qmaxKLgoodbreak+Ceqmax lnqegoodbreak=lnKFgoodbreak+1nlnCe where q max (mg/g) is the maximum adsorption capacity of Cu(II); K L (L/mg) is the Langmuir constant; K F (mg 1−1/ n ·L −1/ n ·g −1 ) is the Freundlich constants and n is Freundlich index.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several sharp peaks belonging to the insolvable mineral products could be also detected; this indicates that the mineral contents in EP could be converted into insoluble ceramics during the high temperature treatment. As shown in Figure 2 a, the FTIR peak centered at ~1049 cm −1 can be ascribed to the COOH or CHO bending vibration, whereas the characteristic peak centered at ~1622 cm −1 occurs due to the C=O stretching vibration [ 33 , 34 ]. The peak intensities of EBC-K correspond with these oxygen content function groups, and they are slightly increased compared with EBC-Na, thus indicating that the population in the surface function group is greatly enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…The molten salt method is an effective strategy that yields carbon materials by adopting a low melting point inorganic salt as the protecting medium instead of commonly used inert atmospheres; this means that it is a low cost and energy saving method that prepares carbon materials for different applications [ 25 , 26 , 27 , 28 , 29 , 30 ]. Based on previous studies, the etching effect of molten salt and the oxygen enriched reaction medium could effectively introduce a hierarchical porous structure as well as rich surface defects, which are favorable for persulfate activation [ 31 , 32 , 33 , 34 ]; however, to the best of our knowledge, few studies have devoted themselves to the preparation of bio-carbons, based on the molten salt method, in order to obtain AOPs and study its economic feasibility by systematic tech-economic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Râpă et al [72] equally found in their biosorption of Cu(II) ions to alginate/clay hybrid composite beads study that the PSO model best described the biosorption process [72]. While in the studies of Bai et al [80], Hu et al [82], and Khan et al [81] where Humulus scandens-derived biochar, biochar derived from Chaenomeles sinensis seed, and muskmelon peel biochar were utilized for the biosorption of Cu(II) ions, it was noticed that the biosorption processes were best close-fitting to the experimental data using the PSO model [86][87][88][89][90][91][92][93]. While in the studies of Sachan and Das [86] and Rahim et al [87] where the biosorption of Cu(II) ions to biochar obtained from plant biomass Saccarum ravvanne and decorated with manganese dioxide and desiccated coconut waste (DCW) effectiveness was assessed, it was noticed that the biosorption process followed the PSO model.…”
Section: Biosorption Kineticsmentioning
confidence: 97%